Immunosuppressive effect of zhankuic acid C from Taiwanofungus camphoratus on dendritic cell activation and the contact hypersensitivity response. Issue 20 (15th October 2015) - Lin, Ming-Kuem; Lee, Meng-Shiou; Chang, Wen-Te; Chen, Hsing-Yu; Chen, Jin-Fu; Li, Yi-Rong; Lin, Chi-Chen; Wu, Tian-Shung
Graphical abstract